(untitled) (International conference on multidisciplinary science, 2025)
This article explores the functional features of terminology in the field of material science in both English and Uzbek languages. Material science terminology serves not only as a linguistic tool but also as a means of knowledge transfer in academic, industrial, and research contexts. The study highlights semantic, structural, and functional aspects of terms, emphasizing the challenges of translation, adaptation, and standardization in a bilingual environment.